Offshore Energy Harvesting of a Marine Floating Pendulum Platform Model - Janzen, Frederic C.; Tusset, Angelo M.; Balthazar, Jose M. [UNESP]; Rocha, Rodrigo T.; Lima, Jeferson J. de [UNESP]; Nabarrete, Airton (Latin Amer J Solids Structures, 2019)
This work presents an analysis of an ocean wave energy harvesting system. This system is composed of a direct current (DC) power generator attached at the middle-top of a floating platform. A pendulum is connected to the generator's shaft. It is considered that the ocean waves motion swings the platform in the vertical direction, which transfers energy to the pendulum, making possible to convert mechanical energy, induced by the ocean wave, into a rotational motion due the pendulum and after in electric energy due the generator. With the objective to optimize the harvested power, several analyses of the pendulum parameters, ocean wave amplitude and frequency were carried out. This work was based on the Brazilian's coast characteristics. Numerical and experimental results were performed which shows the efficiency of the conversion of mechanical energy provided by the pendulum into electric power.
Keywords: Nonlinear Dynamics of Structures; Ocean Space Utilization; Ocean Energy Technology; Mathematical Modeling